Blood far forward: Time to get moving!. (June 2015) - Cap, Andrew P.; Pidcoke, Heather F.; DePasquale, Marc; Rappold, Joseph F.; Glassberg, Elon; Eliassen, Håkon S.; Bjerkvig, Christopher K.; Fosse, Theodor K.; Kane, Shawn; Thompson, Patrick; Sikorski, Robert; Miles, Ethan; et al.
Abstract : ABSTRACT: In planning for future contingencies, current problems often crowd out historical perspective and planners often turn to technological solutions to bridge gaps between desired outcomes and the reality of recent experience. The US Military, North Atlantic Treaty Organization, and other allies are collectively taking stock of 10-plus years of medical discovery and rediscovery of combat casualty care after the wars in Iraq and Afghanistan. There has been undeniable progress in the treatment of combat wounded during the course of the conflicts in Southwest Asia, but continued efforts are required to improve hemorrhage control and provide effective prehospital resuscitation that treats both coagulopathy and shock. This article presents an appraisal of the recent evolution in medical practice in historical context and suggests how further gains in far forward resuscitation might be achieved using existing technology and methods based on whole-blood transfusion while research on new approaches continues.